Dynamics of agricultural wage and rice price in Bangladesh: a re-examination - Rashid, Shahidur (International Food Policy Research Institute, 2002)
Like many other Asian countries, the causal relationship between agricultural productivity and the incidence of rural poverty has been a widely debated subject in Bangladesh. A number of studies argued that the real agricultural wage rate was declining during the period when the country had experienced overall agricultural growth. This paper contributes to this debate in two ways: i) it re-examines the methodological aspects of past studies and presents alternative estimates; and ii) analyzes dynamics of agricultural wage and rice price using the most recent data. Multivariate co-integration techniques are used to examine the long and short-run relationships among agricultural wage rate, rice price, urban wage rate, and other prices. The results show that agricultural wage and rice price maintained strong co-integrating relationships during the periods 1949/50 -1979/80; and the elasticities of agricultural wage rate with respect to rice price are substantially higher than what past studies had reported. Analyses of post-famine data (1976/77-1998/99) suggest that rice price, which was strongly co-integrated with agricultural wage rate until the early 80s, is no longer a significant determinant of wage formation in Bangladesh.